2020
DOI: 10.1007/s10479-020-03611-x
|View full text |Cite
|
Sign up to set email alerts
|

Gresilient supplier assessment and order allocation planning

Abstract: Companies are under pressure to re-engineer their supply chains to 'go green' while simultaneously improving their resilience to cope with unexpected disruptions where the supplier selection decision plays a strategic role. We present a new approach to supplier evaluation and allocating the optimal order quantity from each supplier with respect to green and resilience (Gresilience) characteristics. An integrated framework that considers traditional business, green and resilience criteria and sub-criteria was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 83 publications
3
55
0
Order By: Relevance
“…The findings of this study indicated that sustainability and resilience are interrelated concepts. This in line with the fourth perspective about the sustainability resilience relationship as suggested by the authors of this study in Table 1 and the studies of Higgins et al (2010) and Mohammed et al (2021). However, the findings of this study suggest that the sustainability-resilience relationship is non-linear.…”
Section: Research Implicationssupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of this study indicated that sustainability and resilience are interrelated concepts. This in line with the fourth perspective about the sustainability resilience relationship as suggested by the authors of this study in Table 1 and the studies of Higgins et al (2010) and Mohammed et al (2021). However, the findings of this study suggest that the sustainability-resilience relationship is non-linear.…”
Section: Research Implicationssupporting
confidence: 90%
“…The authors introduce a systems dynamics simulation model to show that the development of sustainable and resilient ASCs restricting the information sharing that causes endogenous demand and utilize a loosely coupled strategy for decision-making to reduce the negative influence of endogenous demand. Mohammed et al (2021) coins the term "gresilient" to combine green and resilient practices. They integrate both with traditional practices for supplier selection.…”
Section: The Sustainability and Resilience Relationshipmentioning
confidence: 99%
“… I18 Supply chain resilience SC resilience define as the SC adaptive ability to respond to disruptions, react to unexpected occasions, and then recover by continuously maintaining operations at the desired balanced of connectedness and control over the SC function and structure. Ponomarov and Holcomb (2009) ; Remko (2020) ; Kumar & Anbanandam (2020) ; Asamoah et al (2020) ; Kahiluoto et al (2020) ; Aslam et al (2020) ; Shekarian & Mellat Parast (2020) ; Piprani et al (2020) ; Mohammed et al (2020) ; Yu et al (2019) ; Ivanov & Sokolov (2019) ; Tan et al (2019) ; López & Ishizaka. (2019) ; Thomas & Mahanty (2019) ; Mikhail et al (2019) ; Singh et al (2019) ; Scholten et al (2019) ; Bevilacqua et al (2019) ; Rajesh (2016) ; Hosseini & Ivanov (2020) ; Behzadi et al (2020) ; Lohmer et al (2020) ; Li & Zobel (2020) .…”
Section: Resultsmentioning
confidence: 99%
“…So, due to the mentioned reasons, focusing on resilience is absolutely necessary for industries. However, traditional sustainable supplier selection process just includes sustainability criteria and the resilient attributes have been neglected by purchasing managers (Amindoust 2018;Mohammed et al 2020). For example, Torabi et al (2015) mentioned that resilience is a kind of management for recognizing the potential disruptions, increasing the ability to control these specified problems and back to the normal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There are examples of lack of focus on resilience which caused big problems for the companies such as company Apple in Japan's earthquake in 2011 (News 2011). Moreover, it has been reported that neglecting this issue has recently affected other industries in UK and USA (Mohammed et al 2020). Thus, providing a resilient supply chain can help industries to be safe from disruptions (Sáenz et al 2018).…”
Section: Introductionmentioning
confidence: 99%